(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
High-temperature industrial furnaces are widely used in metallurgy, glass production, ceramics, and casting processes, where operating temperatures typically range from 800°C to 1600°C. Such extreme conditions pose serious risks to human operators and impose strict technical requirements on equipment. This study analyzes the technological, safety, and economic justification for implementing industrial robotic systems in high-temperature furnace environments. The research integrates mechanical design considerations, thermal management strategies, intelligent control systems, and organizational factors affecting robot deployment. Special attention is given to heat-resistant manipulators, passive and active cooling technologies, sensor protection mechanisms, and AI-based predictive control algorithms. The results demonstrate that robotization significantly enhances occupational safety, improves process stability, and increases energy efficiency. The study also discusses prospects for implementing robotic furnace systems in the context of industrial modernization in Uzbekistan.